PERLINDUNGAN HUKUM BAGI KONSUMEN STUDI KESADARAN HUKUM PEREDARAN DAGING SAPI DI BOYOLALI - Setiyawan, Wahyudi; Absori, Absori; Wardiono, Kelik (Jurnal Penelitian Humaniora, 2020)
The research aimed to describe the public legal awareness about meat distribution and legal protection for the beef consumers through law enforcement efforts at Boyolali District based on a qualitative non-doctrinal approach. Therefore, this focused more on primary data collected by interviews and observations and supported by secondary data collected by library research. The data then were processed for further qualitative analysis. Based on the results of the study it was found that legal protection related to the distribution of healthy and safe meat did not run well as this was influenced by the community legal, namely the knowledge and understanding of law, although it had been supported by good legal attitudes and behavioral factors.